Sex differences in body composition in youth with type 1 diabetes and its predictive value in cardiovascular disease risk assessment. Issue 1 (5th November 2022) - Brener, Avivit; Hamama, Sandy; Interator, Hagar; Ben Simon, Asaf; Laurian, Irina; Dorfman, Anna; Chorna, Efrat; Yackobovitch‐Gavan, Michal; Oren, Asaf; Eyal, Ori; Lebenthal, Yael
Abstract: Background: Women with type 1 diabetes (T1D) are more susceptible than men to cardiovascular disease (CVD). Signs of increased risk may already appear among adolescent girls. Objectives: We explored the contribution of body composition to the development of CVD risk factors among youth with T1D. Methods: One hundred and eighty nine subjects with T1D (mean age 15.3 ± 5.1 years, 55% boys) followed between January 2018–January 2022 were included in this observational study. Sociodemographic and clinical data were extracted from medical files. Body composition was measured by bioelectrical impedance analysis, and muscle‐to‐fat ratio (MFR) z ‐scores were calculated. Logistic regression model assessed the association between body composition (MFR z ‐scores) and evidence of CVD risk factors. Results: Females were characterised by higher median BMI z ‐scores (0.47 vs. 0.04, p  = 0.012), higher fat and truncal fat percentage levels ( p  ≤ 0.001) and lower median MFR z ‐scores (−0.64 vs. −0.25, p  ≤ 0.001), higher median triglyceride (TG) levels (71 vs. 61 mg/dl, p  = 0.05), longer disease duration to initiation of insulin pump therapy ( p  = 0.041), and more time spent in marked hypoglycemia (1 vs. 0.2%, p  = 0.007) than males. Males' MFR z ‐scores were associated with several diabetes‐related parameters (age at diagnosis, CGM metrics, HbA1c and insulin dose), while the females'' MFR z ‐scores were linked to the atherogenic dyslipidemia index (TG:HDL ratio). The odds for CVD risk factors were doubled for every 1 SD decrease in MFR z ‐score (OR = 0.50, CI [0.30–0.84], p  = 0.009) and also increased with age (OR = 1.07, CI [1.004–1.148], p  = 0.038). Conclusions: Body composition measurement has a predictive value in CVD risk assessment in youth with T1D, with unique characteristics and influences in each sex.